Working Conditions of Women Labours: A Review: A Comprehensive Examination of Working Conditions for Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In India, women are an important component of the workforce. According to the Registrar General and Census Commissioner of India, the overall number of female employees in India is 149.8 million, with female workers in rural and urban regions totaling 121.8 and 28.0 million, respectively, according to Census 2011. 35.9 million women work as cultivators, while another 61.5 million work as agricultural labourers, out of a total workforce of 149.8 million women. The remaining female employees are divided into two groups 8.5 million in the domestic industry and 43.7 million in other occupations. In this paper discuss the women labour and women labour working condition.